Kajian Struktur Dan Karakter Tokoh Pada Pertunjukan Fragmentari Jatayu Antaka - Aryanata, I Made Agus; Yulianggreni, Ni Luh Eka (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Fragmentary has a value that is classified as structured and has sacred value because it is taken from historical epics or great stories of previous times. When viewed from its function, the Jatayu Antaka fragmentary is a dance that is classified as a type of Balinese dance, namely dance art whose elements and basics are based on from the ancestors or not is the art of guardian dance or bebali dance.This research aims to find out what structure is used in the Jatayu Antaka fragmentary and what values ​​are contained in the Jatayu Antaka fragmentary. By providing general and theoretical benefits, namely to describe in more depth the structure and values ​​contained in the Jatayu Antaka fragmentary held by the percussion student activity unit (UKM).This jatayu antaka fragmentation was held to ensure that the percussion student activity unit (UKM) could continue to exist and be more successful in being creative and innovating in producing better works in the field of art, especially musical percussion. Through this fragmentary activity, the Percussion Student Activity Unit (UKM) wants to show that Percussion UKM can still exist because previously it was considered to be in suspended animation because it was thought to rarely have activities. Based on the results of the researcher's observations, the structure of the Jatayu Antaka fragmentary performance has aesthetic value, based on Hindu aesthetics, namely sad angga and from each of the characters in the Jatayu Antaka fragmentary performance we can take the meaning and application examples according to the teachings of Panca Satya.